CD146‐Targeted Multimodal Image‐Guided Photoimmunotherapy of Melanoma. Issue 9 (27th February 2019) - Wei, Weijun; Jiang, Dawei; Ehlerding, Emily B.; Barnhart, Todd E.; Yang, Yunan; Engle, Jonathan W.; Luo, Quan‐Yong; Huang, Peng; Cai, Weibo
Abstract: For melanoma resistant to molecularly targeted therapy and immunotherapy, new treatment strategies are urgently needed. A molecularly targeted theranostic pair may thus be of importance, where the diagnostic probe facilitates patient stratification and the therapeutic companion treats the selected cases. For this purpose, flow cytometry is used to assess the CD146 level in melanoma cells. Based on YY146, a CD146‐specific monoclonal antibody, an imaging probe 89 Zr‐Df‐YY146 is synthesized and its diagnostic performance is evaluated by positron emission tomography (PET) imaging. Furthermore, a photoimmunotherapy (PIT) agent IR700‐YY146 is developed and the therapeutic effect of IR700‐YY146 PIT is assessed comprehensively. CD146 is highly expressed in A375 and SK‐MEL‐5 cells. 89 Zr‐Df‐YY146 PET readily detects CD146‐positive A375 melanomas. Tumor accumulation of 89 Zr‐Df‐YY146 peaks at 72 h with an uptake value of 26.48 ± 3.28%ID g −1, whereas the highest uptake of the nonspecific 89 Zr‐Df‐IgG is 4.80 ± 1.75%ID g −1 . More importantly, IR700‐YY146 PIT effectively inhibits the growth of A375 tumors, owing to production of reactive oxygen species, decreased glucose metabolism, and reduced expression of CD146. To conclude, 89 Zr‐Df‐YY146 and IR700‐YY146 are a promising theranostic pair with the former revealing CD146 expression in melanoma as a PET probe and the latter specifically treating CD146‐positive melanoma as an effective PIT agent. Abstract : Melanoma is a deadly disease with a dismal prognosis . Developing novel theranostic approaches for this malignancy is highly desired. CD146 is a promising biomarker for melanoma. CD146‐specific positron emission tomography imaging with 89 Zr‐Df‐YY146 and photoimmunotherapy with IR700‐YY146 are a promising theranostic pair that may optimize the clinical management of melanomas.